Evaluation of Growth Performance and Feed Efficiency in Exotic Chicken Breed Crosses Involving Fayoumi - Negash, Fikrineh; Abegaz, Solomon; Tadesse, Yosef; Jembere, Temesgen; Esatu, Wondmeneh; Dessie, Tadelle (SSRN, 2022)
The present study aimed to investigate the relative performance of crossbreds generated through reciprocal mating of Fayoumi (FM) with Koekoek (KK), Sasso (SS), and White Leghorn (WL), and the purebred parents for growth and feed efficiency traits. Birds were weighed individually at hatch and every four weeks to 20 weeks to determine body weight (BW) and body weight gain (BWG). Feed intake for each genetic group was used to estimate feed conversion ratio (FCR). Results revealed that significant differences (p < 0.001) existed among the genotypes in BW, BWG, and FCR. For these genotypes, SS outperformed all other genotypes throughout the study period. Reciprocal crosses of FM and SS performed better than the remaining seven genotypes, with KK and reciprocal crosses of KK and FM showing intermediate performance, while FM and WL and reciprocal crosses involving them performed least. Mating FM males with SS, KK, and WL produce crossbreds that outperformed their reciprocal crosses, suggesting that FM has a higher combining ability. Thus, females of these genotypes could be crossed with the third breed to generate crossbreds having higher feed efficiency and growth rates. The results also revealed that crossbreds had higher performance than FM and sometimes their other exotic parents. In most instances, reciprocal crosses of FM with KK and WL outperformed both of their parents in the growth and feed efficiency traits. Therefore, these genotypes could be used in any crossbreeding system to exploit the heterotic effects that existed in them, thereby improving the growth and feed efficiency traits.